Kinetics of Targeted Phage Rescue in a Mouse Model of Systemic Escherichia coli K1. (11th July 2018) - Schneider, György; Szentes, Nikolett; Horváth, Marianna; Dorn, Ágnes; Cox, Alysia; Nagy, Gábor; Doffkay, Zsolt; Maróti, Gergely; Rákhely, Gábor; Kovács, Tamás
Abstract : Escherichia (E.) coli K1 strains remain common causative agents of neonatal sepsis and meningitis. We have isolated a lytic bacteriophage (ΦIK1) against E. coli strain IHE3034 and tested its specificity in vitro, as well as distribution and protective efficacy in vivo . The phage was shown to be specific to the K1 capsular polysaccharide. In the lethal murine model, a high level of protection was afforded by the phage with strict kinetics. A single dose of 1 x 10 8 phage particles administered 10 and 60 minutes following the bacterial challenge elicited 100 % and 95 % survival, respectively. No mice could be rescued if phage administration occurred 3 hours postinfection. Tissue distribution surveys in the surviving mice revealed that the spleen was the primary organ in which accumulation of active ΦIK1 phages could be detected two weeks after phage administration. These results suggest that bacteriophages have potential as therapeutic agents in the control of systemic infections.